Implementation of web-based online ordering applications for MSMEs in Ciharalang Village, Ciamis Regency - Supriatman, Rian Dwicahya; Sidiq, Maulana; Thoyyibah, Luthfiyatun; Pascima, Ida Bagus Nyoman; Fitriani, Rani Ligar (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2023)
This community service is intended to provide solutions to the problems experienced by a partner named UMKM Usaha Laksana Mandiri (MSMEs Usaha Laksana Mandiri), namely the low marketing literacy of trade. In implementing the objectives of this community service, an instructional method is adopted which has three stages of implementation, namely 1) socialization of the use of online sales media, 2) training in making designs and packaging goods, and 3) training in inputting data on goods to be sold in the admin menu. After going through several stages, there are several positive results from the implementation of this community service, including 1) understanding the use of online marketing information technology, 2) attractive product packaging strategies, and 3) sales skills through online marketing media by UMKM Usaha Laksana Mandiri.